EFFICIENCY OF USING BAKED SOIL ON REMOVING SOME HEAVY METALS FROM DIFFERENT WATER SOURCES - & et al., Thaher (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A laboratory experiment was carried out to study the effect of unbaked soil and baked soil burned at 4000C and 9000C as filters to remove some heavy metals (Mn,Cu,Pb,Cd) from three water sources (waste water, Shatt al-Arab and Shatt al-Basra) at four periods (0 , 1/2 , 1, 24 hours. Concentrations of these heavy metals were estimated before and after passing through these filters , and removal efficiency was calculated . The results showed that baked soil at 9000C had the highest removal efficiency compared with that of 4000C and without baking. Filtration at 24 hours was the best among other studied periods. The highest removal efficiencies were 95.20% foe Mn at Shatt al-Arab , 67.83% for Cu at Shatt al-Basra , 66.13% for Pb at Shatt al-Basra and 82.82% for Cd at Shatt al-Arab.